How to identify trust and reciprocity - Cox, James C. (Games and economic behavior, 2004)
This paper uses a three-games (or triadic) design to identify trusting and reciprocating behavior. A large literature on single-game trust and reciprocity experiments is based on the implicit assumption that subjects do not have altruistic or inequality-averse other-regarding preferences. Such experimental designs test compound hypotheses that include the hypothesis that other-regarding preferences do not affect behavior. In contrast, experiments with the triadic design do discriminate between transfers resulting from trust or reciprocity and transfers resulting from other-regarding preferences that are not conditional on the behavior of others. Decomposing trust from altruism and reciprocity from altruism or inequality aversion is critical to obtaining empirical information that can guide the process of constructing models that can increase the empirical validity of game theory.